Shade: uma estratégia seletiva para mitigar ataques DDOS na camada de aplicação em redes definidas por software - Corrêa, João Henrique Gonçalves (2017)
The process of evolution of computers has reached the point that information before distant, are just a user click away. With the development of technology, there have also been developments in mechanisms that threaten the security of information, including the availability of certain information. The denial of Service (DoS) or a distributed form (DDoS) attacks are among the most important business impacts nowadays, affecting service availability severely. Application Layer Denial of Service attacks exploit vulnerabilities protocols, such as HTTP and SIPprotocols. The main challenge in mitigating such attacks is due to the fact that attacker requests have the same status as legitimate clients. This paper proposes the use of ﬁngerprinting techniques for dynamic whitelist in order to mitigate denial of service attacks at the application layer. Fingerprinting allows for more accurate identiﬁcation of a user within a network ﬂow by monitoring parameters such as operating system,browser and IP used. The effectiveness of the technique was demonstrated through experiments carried out in a controlled network, in which, without the use of the technique, a web Application was only able to serve 17% of the clients during a Get-Flooding attack, whereas with the use of the dynamic whitelist the availability rose to more than 99%.